Aflibercept for age-related macular degeneration: 4-year outcomes of a 'treat-and-extend' regimen with exit-strategy. Issue 2 (30th October 2020) - Jaggi, Damian; Nagamany, Thanoosha; Ebneter, Andreas; Munk, Marion; Wolf, Sebastian; Zinkernagel, Martin
Abstract : Aim: To report long-term outcomes on best-corrected visual acuity (BCVA) and treatment intervals with a treat-and-extend (T&E) regimen in patients with neovascular age-related macular degeneration (nAMD). Methods: This observational study included treatment-naïve patients with nAMD, treated with aflibercept. A specific T&E protocol without a loading phase and predefined exit criteria was administered. After reaching predefined 'exit-criteria', the treatment period was complete, and patients were observed three monthly. Results: Eighty-two patients with a follow-up period of ≥2 years were included. BCVA (mean±SD, ETDRS letters) increased from 51.9±25.2 at baseline to 63.7±17.7 (p<0.0001) at 1 year, 61.7±18.5 (p<0.0001) at 2 years, 62.4±19.5 (p<0.0001, n=61) at 3 years and remained insignificantly higher than baseline at 4 years at 58.5±24.3 (p=0.22). Central subfield thickness (mean±SD, μm) decreased significantly from 387.5±107.6 (p<0.0001) at baseline to 291.9±65.5 (p<0.0001) at 1 year, and remained significantly lower until 4 years at 289.0±59.4 (p<0.0001). Treatment intervals (mean±SD, weeks) could be extended up to 9.3±3.1 weeks at 1 year and remained at 11.2±3.5 weeks at 4 years. Twenty-nine (35%) patients reached exit criteria and continued with three monthly observation only. Conclusions: After 4 years of treatment, initial vision gains were maintained with a reasonable treatment burden, even without an initial loading phase. Our results on functional outcomes are comparable with large controlled studies.